SFB754 Downcore proxy records - Renato Salvatteci; Hela Mehrtens (PANGAEA, 2021)
One of the objectives of the SFB 754 was the reconstruction of the factors controlling the intensity and the spatial extent of the OMZ in the Eastern Tropical Pacific, specifically off Peru, since the Last Glacial Maximum (21000 years ago). For the purpose of these paleoceanographic studies, long gravity cores were recovered during four scientific expeditions (M77/1, M77/2, M92, and M135; see Figure 4). During the cruises M77/1 and M77/2 in 2008, 51 sediment cores were retrieved below and in the centre of the OMZ, from ~17° S to the equator (Pfannkuche et al., 2011; see Figure 4). Most of the records collected in the core of the OMZ (i.e. ~200 to ~500 m depth), from ~8 to 15° S, show sedimentary discontinuities during the Holocene (last 11700 years), which preclude high resolution paleoceanographic reconstructions in this area (Erdem et al., 2016; Salvatteci et al., 2014, 2016). Based on the information collected during M77/1 and M77/2 and also on the scientific literature, cruise M135 aimed specifically at finding the most complete Holocene sequence in the Eastern Tropical South Pacific. For this purpose, a detailed paleoceanographic survey took place at ~17° S, an area that is less affected by processes that can produce sediment discontinuities. Six sediment cores were retrieved, two of which contained the most complete sediment sequences for the last 10 000 years (Salvatteci et al., 2019).